Event-triggered zeroing dynamics for motion control of Stewart platform - Shuai Li (Journal of the Franklin Institute, 2020)
Zeroing dynamics (ZD) was originally proposed and investigated for solving time-varying problems. Due to its advantages in convergence and accuracy, ZD has been successfully extended to various areas, including automatic control, robotics and numerical computation. In this paper, we further propose a novel one called event-triggered zeroing dynamics (ETZD) by incorporating the event-triggered strategy to improve the practicability of ZD. Absorbing the advantages of event-triggered strategy, ETZD can not only significantly reduce the consumption on computation but also maintain the original advantages of ZD. For better understanding, we employ ETZD to design a specific motion controller of a popular type of robot manipulators (i.e., Stewart platform). The stability of the motion controller is presented and analyzed via Lyapunov analysis. Furthermore, two different shaped path tracking tasks are executed in numerical experiments, and compared with conventional ZD controllers, to illustrate the advantage in convergence, accuracy and practicability of ETZD controller.